Greening up Local Taxes (an Environmental Approach to Municipal Taxation from a Spanish Perspective) - Herrera, Pedro M. (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
Spanish local taxes and charges are not adequately designed to protect the environment. Nevertheless, most of them include tax credits to foster environmentally friendly activities (e.g. installation of solar panels or acquisition of electric vehicles). Our paper deals with the current legislation and proposes reforms to improve the environmental role of local taxes and charges.